Total chemical synthesis of glycocin F and analogues: S-glycosylation confers improved antimicrobial activity. Issue 6 (12th January 2018) - Amso, Zaid; Bisset, Sean W.; Yang, Sung-Hyun; Harris, Paul W. R.; Wright, Tom H.; Navo, Claudio D.; Patchett, Mark L.; Norris, Gillian E.; Brimble, Margaret A.
Abstract : Replacing the O -linked saccharide in the bacteriocin glycocin F with an S -linked version results in a peptidomimetic that increases the bacteriostatic effect. Abstract : Glycocin F (GccF) is a unique diglycosylated bacteriocin peptide that possesses potent and reversible bacteriostatic activity against a range of Gram-positive bacteria. GccF is a rare example of a 'glycoactive' bacteriocin, with both the O -linked N -acetylglucosamine (GlcNAc) and the unusual S -linked GlcNAc moiety important for antibacterial activity. In this report, glycocin F was successfully prepared using a native chemical ligation strategy and folded into its native structure. The chemically synthesised glycocin appeared to be slightly more active than the recombinant material produced from Lactobacillus plantarum . A second-generation synthetic strategy was used to prepare 2 site selective 'glyco-mutants' containing either two S -linked or two O -linked GlcNAc moieties; these mutants were used to probe the contribution of each type of glycosidic linkage to bacteriostatic activity. Replacing the S -linked GlcNAc at residue 43 with an O -linked GlcNAc decreased the antibacterial activity, while replacing O -linked GlcNAc at position 18 with an S -linked GlcNAc increased the bioactivity suggesting that the S -glycosidic linkage may offer a biologically-inspired route towards more active bacteriocins.